Edaravone protects rats against oxidative stress and apoptosis in experimentally induced myocardial infarction: Biochemical and ultrastructural evidence. (November 2015) - Hassan, Md Quamrul; Akhtar, Md Sayeed; Akhtar, M.; Ali, Javed; Haque, Syed Ehtaishamul; Najmi, Abul Kalam
Abstract : Objectives: The present study was designed to evaluate the cardioprotective potential of edaravone on oxidative stress, anti-apoptotic, anti-inflammatory and ultrastructure findings in isoproterenol (ISO) induced myocardial infarction (MI) in rats. Methods: Rats were pretreated with edaravone (1, 3, 10 mg/kg body weight-1 day-1) intraperitoneally. MI was induced by subcutaneous administration of ISO (85 mg/kg body weight-1) at two doses with 24h interval. Results: ISO treated rats showed significant increase in the levels of thiobarbituric acid reactive substances (TBARS) and decreased levels of reduced glutathione, glutathione perdoxidase, glutathione reductase and glutathione-S- transferase in the cardiac tissues. Moreover, significant increase in the levels of lactate dehydrogenase (LDH), creatine kinase-MB (CK-MB), C - reactive protein and caspase-3 activity was observed in ISO treated group. Pretreatment of ISO intoxicated rats with edaravone showed significant decrease in the level of TBARS, increased activities of antioxidant enzymes and significantly decreased levels of LDH and CK-MB. Moreover, results also showed decreased C-reactive protein level, caspase-3 activity and maintained ultrastructure of the myocardial cells. Discussion: Our study suggests that edaravone possess strong cardioprotective potential. Edaravone may have exhibited cardioprotective effects by restoring antioxidant defense mechanism, maintaining integrity of myocardial cell membrane, reducing apoptosis and inflammation against ISO induced MI and associated oxidative stress.